Economy during a simulated laboratory test triathlon is highly related to Olympic distance triathlon - Miura, H.; Kitagawa, K.; Ishiko, T. (International Journal of Sports Medicine, 1997)
This study examined the relationship between Olympic distance triathlon (swim over 1.5 km, cycle over 40.0 km, and run over 10.0 km) and economy during a simulated laboratory test triathlon. Seventeen male triathletes conducted both maximal exercise tests and simulated laboratory triathlon. The latter test consisted of swimming (S), cycling (C) and running (R) stages as a continuous task using a flume-pool, a cycle ergometer and a treadmill, respectively. The exercise intensity and duration were 60% of VO2max during swimming, cycling and running for 30, 75 and 45 min, respectively. The index of economy was determined by the % VO2max at the last min of each stage during a simulated laboratory test triathlon. Results indicated that Olympic distance triathlon (total time) was correlated to swimming-VO2max (r = -0.621, p < 0.001), cycling-VO2max (r = -0.873, p < 0.001), running-VO2max (r = -0.891, p < 0.001), S-Economy (r = 0.208, ns), C-Economy (r = 0.601, p < 0.001) and R-Economy (r = 0.769, p < 0.001). There were also significant correlations between swimming time and swimming-VO2max (r = -0.648, p < 0.01), between cycling time and cycling-VO2max (r = -0.819, p <0.001), between running time and running-VO2max (r = -0.726, p < 0.001), between swimming time and S-Economy (r = 0.550, p < 0.05), between cycling time and C-Economy (r = 0.613, p < 0.01), and between running time and R-Economy (r = 0.548, p < 0.05). These results demonstrated that the larger VO2max during maximal exercise tests and smaller increment of VO2 during a simulated laboratory test triathlon indicating good economy were good predictors to determine the Olympic distance triathlon.